EMPOWERING SMALL-SCALE CATTLE FARMERS THROUGH TECHNOLOGICAL INNOVATION IN FEED RESOURCE FINANCING - Sintya J K Umboh; Boyke Rorimpandey; Merry A. V. Manese; Merci Rosyanty Waani; Tilly F.D. Lumy (Halu Oleo University, 2025)
Small-scale cattle farmers face persistent challenges in managing feed costs, which constitute a major component of production expenses. Limited access to technology and financial literacy often hinders their ability to improve efficiency and sustain operations. This study aims to evaluate the effectiveness of a technology-based training model in enhancing farmers’ competencies in feed cost management. Five key indicators were assessed: understanding of hidden costs, identification of forage cost components, proficiency in using Visual Basic applications, ability to construct livestock cash flow, and awareness of the importance of cost recording. A quantitative approach was employed using a pre-test and post-test design involving ten participants, with data analysed through the Wilcoxon Signed-Rank test. Results revealed statistically significant improvements across all indicators (Z = -2.803; p = 0.0051), with average score increases ranging from 79.4% to 102.4%. These findings demonstrate that practice-oriented and digitally integrated training effectively strengthens both technical and managerial capacities among small-scale cattle farmers. The proposed training model is suitable for replication in broader farmer empowerment programs and provides a foundation for longitudinal evaluation of its long-term impact on efficiency, profitability, and business resilience.